Dialectics of Fasad and Musibah in the Qur'an as Ethical Framework for Anthropogenic Damage - 'Ammar 'Abdulmatin; Ahmad Nurrohim (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the concepts of fasad (corruption/damage) and musibah (calamity/disaster) in the Qur’an and their relevance to environmental damage caused by anthropogenic activities. The study focuses on the relationship between human actions, ecological imbalance, and disasters from the perspective of Qur’anic ethics. This research uses a qualitative comparative method through thematic exegesis and content analysis of Qur’anic verses and scientific literature on Islamic environmental ethics. Data were collected through library research and analyzed by grouping concepts related to fasad, musibah, khilafah, and mizan. The findings show that fasad refers to human actions that damage moral, social, and ecological balance, while musibah is understood as the consequence of such damage. The Qur’an also emphasizes human responsibility as khalifah to maintain environmental balance and prevent destruction. This study concludes that the concepts of fasad and musibah provide a relevant Qur’anic environmental ethics framework for understanding contemporary ecological crises and contribute to the development of thematic Qur’anic exegesis and Islamic environmental ethics.